Pengembangan Media Ajar Berbasis Multimedia Di SMA Negeri 1 Talawi - Nofriadi N; Herman Saputra; Adi Prijuna Lubis; Suparmadi S (LPPM STIKOM Tunas Bangsa, 2020)
Community service activities titled Multimedia-Based Teaching Media Development in the State High School 1 Talawi which aims to provide knowledge to all teachers in the Talawi 1 High School environment. The method used in this activity is to conduct workshops in creating and developing teaching media using power point applications. During the activity all the teachers are guided in making each other's teaching materials in accordance with the subjects held in the Talawi 1 High School environment. The final result of this dedication is that all teachers can create and develop computerized based teaching materials by using power point applications.